Use of Vaginal Misoprostol Prior to Placement of an Intrauterine Device: A Review - Elizabeth Hoover; Abbey Hardy- Fairbanks; Colleen K Stockdale (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2017)
Intrauterine devices (IUD) are a highly effective and safe form of contraception. However, many individuals, particularly nulligravidas, elect against IUD use due to fear of pain associated with insertion. Misoprostol has been proposed as an agent to ease IUD insertion and decrease associated pain. However, its efficacy in the literature is inconclusive and its use varies widely between healthcare providers. We present a review on the efficacy of vaginal misoprostol in facilitating IUD insertion and reducing procedureassociated pain.